A Comparative Study of Maṣlaḥah and Mischief Rule: Pakistani Perspective - Razi, Naseem (Journal of Islamic Thought and Civilization, 2021)
At present, almost all the legal systems are concerned with establishing a flexible interpretive policy to make the law to resolve the everyday complex issues for the benefit of the people at large. It is, however, a matter of great concern that the higher courts in Pakistan are still following static and foreign interpretive modes like a literal rule, the golden rule, and mischief rule etc, in the presence of dynamic interpretive principles of Islam. In this context, this research aims to analyze critically, the mischief rule and to present maslahah, a vibrant Islamic interpretive principle. This article argues that the Holy Prophet (SAW), his companions and the traditional Muslim jurists had to decide the contemporary issues by the way of maṣlaḥah which led to the development of Islamic jurisprudence and resulted in the ease of the people. While interpretive rules of English common law are static and have become outdated. This research, thus, concludes that unlike mischief rule, maslaha is more flexible and favorable by Islam for resolving the present-day socio-economic issues of the people. It recommends the higher courts of Pakistan to follow the principle of maṣlaḥah during the process of interpretation. It is also acclaimed that the Renaissance of this vibrant principle of ijtihād would be a revival of the interpretive policy of the Prophet (SAW), his companions and the traditional Muslim jurists. It would also lead to the development of Islamic jurisprudence in the light of changed context. Keywords: Maṣlaḥah, Mischief rule, Judicial policy, Pakistani context, Conclusions and recommendations